PENGARUH TINGKAT KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH BANK PERKREDITAN RAKYAT LOGO KARO ASRI BERASTAGI - Sembiring, Menanti; Br Karo, Salsalina (Universitas Medan Area, 2018)
This research aimed to know the influence of satisfaction and trust to the customer loyality in PT Bank Perkreditan Rakyat Logo Karo Asri Berastagi. Population of this research is about 1881Bof people and to be taken about 95 of people to become sample.Technique of collecting data which is used is by questioner that by doing sharing questioner to respondent. Technique of analyzing data which is used is Multiple Linier Regression. The result of this research showed that partially, satisfaction and trust influence to the customer loyality in PT. Bank Perkreditan Rakyat Logo Karo Asri Berastagi. Simultaneously,satisfaction and trust also to the customer loyality in PT. Bank Perkreditan Logo Karo Asri Berastagi.Adjusted R Squere amount to 0,500 which mean 50 % customer loyality in PT. Bank Perkreditan Rakyat Logo Karo Asri Berastagi was influence by satisfaction and trust while the residual 50% was influence by the other factors. Keywords : Satisfaction,trust, loyality